ANALYSIS OF VILLAGE ALLOCATION OF FUNDS ON WOMEN'S EMPOWERMENT IN JANGAN - JANGAN VILLAGE, PUJANANTING SUB-DISTRICT, BARRU DISTRICT - Jumria; Marsuki; Sunarti (Meraja journal, 2023)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal